1993
DOI: 10.1227/00006123-199305000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Basis of Syringomyelia Occurring with Hindbrain Lesions

Abstract: Hindbrain lesions that distort or compress the cervicomedullary junction are commonly associated with syringomyelia. As a basis for discussing pathogenetic mechanisms, the upper end of the central canal of the spinal cord was examined histologically in six aborted fetuses and 14 adults dying of natural causes; the results were correlated with magnetic resonance images in 40 normal subjects. The central canal of the medulla, which extends from the cervicomedullary junction to the fourth ventricle, was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Furthermore, these were cases of deformation or hydrocephalus with blockage of the outlet of the fourth ventricle. It has been reported that syringomyelia following blockage of the outlet of the fourth ventricle was due to central canal enlargement (hydromyelia) that was caused by inflow from the ventricles [13,18]. Hence, we suspected that the syringomyerlia of this cat was due to a hydromyelia because hydrocephalus, enlargement of the fourth ventricle, and an ependymal lining the inner wall of the syrinx were detected.…”
mentioning
confidence: 73%
“…Furthermore, these were cases of deformation or hydrocephalus with blockage of the outlet of the fourth ventricle. It has been reported that syringomyelia following blockage of the outlet of the fourth ventricle was due to central canal enlargement (hydromyelia) that was caused by inflow from the ventricles [13,18]. Hence, we suspected that the syringomyerlia of this cat was due to a hydromyelia because hydrocephalus, enlargement of the fourth ventricle, and an ependymal lining the inner wall of the syrinx were detected.…”
mentioning
confidence: 73%
“…Ball and Dayan1 argued that CSF enters the syrinx through the perivascular spaces when the spinal subarachnoid pressure is increased during coughing or straining. Several authors3 4 6 16 17 supported the theory of entrance of CSF from the subarachnoid space via the perivascular spaces. Milhorat et al 3 proposed that the central canal would function as a sink that is capable of clearing substances from the parenchymal tissue of the spinal cord to the fourth ventricle.…”
Section: Discussionmentioning
confidence: 94%
“…Subsequent authors have highlighted the lack of communication between the syrinx and fourth ventricle and postulated that the fluid entered the syrinx from the spinal subarachnoid space. 6,9,10 With the advent of dynamic MR imaging and intraoperative sonography, Oldfield et al 6 proposed that the downward movement of the tonsils seen during systole caused a "pistonlike" effect, resulting in a CSF pressure wave that contracted the cord and forced fluid into it. Researchers argued, however, that if fluid pressure caused the cord to contract, it would be unlikely that any fluid could enter the cord.…”
Section: Discussionmentioning
confidence: 99%